DISPLACEMENT AND LUMINESCENCE OF EU3+ IN CAYBO4 - Zeng X.Q.; Hong G.Y.; You H.P.; Kim C.H.; Pyun C.H. (My University, 2000)
CaY1-xBO4: xEu was synthesied by solid state reaction method, and the displacement and luminescence of the Eu3+ in CaYBO4 host were studied. Two luminescent centers could be observed at certain Eu3+ -concentration, indicating that the Eu3+ occupies two different crystallographic sites. This result shows that the Eu3+ occupies two different Y3+ sites in CaYBO4. The investigation on Eu-O charge transfer bands indicates that the larger distortion or the lower symmetry of Eu3+ site is, the shorter wavelength of the Eu-O charge transfer band is. When the Eu3+-concentration is high (x > 0.10), Eu3+ occupies the sites of Ca2+ and is reduced to Eu2+.